A manifestação do grotesco nos romances de Lúcio Cardoso - Paula Francioli de Sousa (2013)
In this paper we investigate the manifestation of grotesque images in the novels of Lúcio Cardoso. Our main objective was to demonstrate how the themes constantly approached by writer, regarded as unpleasant, like death, disease, moral decay, mental and physical, coupled with a poetic language, part of a universe of grotesque in his novels. The presence of the grotesque (intentional or not) in a work raises the level of criticism of the concepts crystallized and a conservative society and expresses the writer's creative freedom. Furthermore, the presence of unpleasant subjects contributes to the structure of stylistic design for a good track novelist by the Lúcio Cardoso. In this project Lúcio Cardoso argues that a novelist's obligation to take their characters to the highest degree of despair and anguish, for it is in these moments that the being reveals itself.